Temple of the ruby of fire - Stilton, Geronimo (New Delhi Scholastic, 2025)
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. It was my most thrilling adventure yet! My old friend Professor von Volt had discovered the location of the famous Ruby of Fire and before I could let out a squeak of protest, my sister Thea had dragged me into race to be the first to find the legendary gem. The jewel was protected by thousands of ancient booby-traps a 'fraidy mouse's worst nightmare? Would I make it through with my fur?
Keywords: Children Fiction